Statistical isomorphism of three-level fractional factorial designs - Tsai, Pi-Wen; Gilmour, Steven G.; Mead, Roger (Utilitas Mathematica, 2006)
From a statistician's standpoint, the interesting kind of isomorphism for fractional factorial designs depends on the statistical application. Combinatorially isomorphic fractional factorial designs may have different statistical properties when factors are quantitative. This idea is illustrated by using Latin squares of order 3 to obtain fractions of the 33 factorial design in 18 runs.